TANGGAPAN TANAMAN JAGUNG MANIS AKIBAT PEMBERIAN KOMPOS JERAMI DAN HARA - Edyson Indawan (BUANA SAINS, 2006)
This study was aimed to explore of plant affectivity in using its environmental resources and to quantitatively solve problems related to growth of sweet corn. Twelve treatments comprising four levels of rice straw application and three levels of nutrient application was arranged in a randomized block design with three replicates. The results showed that a combination of 10 t rice straw/ha with 400 kg Urea, 35 kg TSP, and 250 kg KCl /ha produced the highest stem dry weight. There was no interaction between leaf dry weight, root dry weight and cop dry weight of the plant